Turbidity weakens selection for assortment in body size in groups - Kimbell, Helen S.; Morrell, Lesley J. (Behavioral ecology, 2016)
Prey animals commonly associate with similar-looking individuals to reduce predation risk, via a reduction in predator targeting accuracy (the confusion effect) and preferential targeting of distinct individuals (the oddity effect). These effects are mediated by body size, as predators often preferentially select large-bodied individuals, which are therefore at an increased risk within a group. The selection pressure to avoid oddity by associating with similar sized group mates is stronger for large individuals than small. This selection depends on the ability of both predators and prey to accurately assess body size and respond accordingly. In aquatic systems, turbidity degrades the visual environment and negatively impacts on the ability of predators to detect (and consume) prey. We assessed the effect of algal turbidity on predator–prey interactions in the context of the oddity effect from the perspective of both predator and prey. From a predator’s perspective, we find that 9-spined sticklebacks preferentially target larger Daphnia in mixed swarms in clear water, but not in turbid water, although the difference in attack rates is not statistically significant. When making shoaling decisions, large sticklebacks preferentially associate with size-matched individuals in clear water, but not turbid water, whereas small individuals showed no social preference in either clear or turbid water. We suggest that a reduced ability or motivation to discriminate between prey in turbid water relaxes the predation pressure on larger prey individuals allowing greater flexibility in shoaling decisions. Thus, turbidity may play a significant role in predator–prey interactions, by altering predator–prey interactions.
Keywords: Confusion effect; Group living; Oddity; Shoaling; Visual environment